Allylic alcohols and amines by carbenoid eliminative cross-coupling using epoxides or aziridines - Fleming, Matthew J.; Hodgson, David M. (Beilstein Journal of Organic Chemistry, 2021)
α-Lithiated terminal epoxides and N-(tert-butylsulfonyl)aziridines undergo eliminative cross-coupling with α-lithio ethers, to give convergent access to allylic alcohols and allylic amines, respectively. The process can be considered as proceeding by selective strain-relieving attack (ring-opening) of the lithiated three-membered heterocycle by the lithio ether and then selective β-elimination of lithium alkoxide.
Keywords: alkenes; aziridines; epoxides; lithiation; synthetic methods

Preparation of Alkenes, A Practical Approach - Williams, J. M. J. (Oxford University Press, 1996)

(untitled) - Blakemore, P. R.; Hoffmann, R. W. (Angew. Chem., Int. Ed., 2018)

(untitled) - Hodgson, D. M.; Bray, C. D.; Kindon, N. D. (Org. Lett., 2005)

(untitled) - Hodgson, D. M.; Miles, S. M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hodgson, D. M.; Humphreys, P. G.; Miles, S. M.; Brierley, C. A. J.; Ward, J. G. (J. Org. Chem., 2007)

(untitled) - Kaufman, T. S. (Synlett, 1997)

(untitled) - Dechoux, L.; Doris, E.; Mioskowski, C. (Chem. Commun., 1996)

(untitled) - Hodgson, D. M.; Stent, M. A. H.; Wilson, F. X. (Synthesis, 2002)

(untitled) - Hodgson, D. M.; Bray, C. D.; Kindon, N. D. (J. Am. Chem. Soc., 2004)

(untitled) - Hodgson, D. M.; Bray, C. D.; Kindon, N. D.; Reynolds, N. J.; Coote, S. J.; Um, J. M.; Houk, K. N. (J. Org. Chem., 2009)

(untitled) - Michnick, T. J.; Matteson, D. S. (Synlett, 1991)

(untitled) - Alcaraz, L.; Harnett, J. J.; Mioskowski, C.; Martel, J. P.; Le Gall, T.; Shin, D.-S.; Falck, J. R. (Tetrahedron Lett., 1994)

(untitled) - Alcaraz, L.; Cridland, A.; Kinchin, E. (Org. Lett., 2001)

(untitled) - Still, W. C. (J. Am. Chem. Soc., 1978)

(untitled) - Linderman, R. J.; Siedlecki, J. M. (J. Org. Chem., 1996)

(untitled) - Gadwood, R. C.; Rubino, M. R.; Nagarajan, S. C.; Michel, S. T. (J. Org. Chem., 1985)

(untitled) - Magnus, P.; Roy, G. (Organometallics, 1982)

(untitled) - Orita, A.; Yoshioka, N.; Struwe, P.; Braier, A.; Beckmann, A.; Otera, J. (Chem. – Eur. J., 1999)

(untitled) - Hodgson, D. M.; Fleming, M. J.; Stanway, S. J. (Org. Lett., 2005)

(untitled) - Hodgson, D. M.; Štefane, B.; Miles, T. J.; Witherington, J. (Chem. Commun., 2004)

(untitled) - Hodgson, D. M.; Štefane, B.; Miles, T. J.; Witherington, J. (J. Org. Chem., 2006)

(untitled) - Azzena, U.; Pilo, L.; Sechi, A. (Tetrahedron, 1998)

(untitled) - Kim, J. D.; Han, G.; Jeong, L. S.; Park, H.-J.; Zee, O. P.; Jung, Y. H. (Tetrahedron, 2002)

(untitled) - Caubere, P.; Moreau, J. (Tetrahedron, 1970)

Organolithiums: Selectivity for Synthesis - Clayden, J. (Pergamon Press, 2002)